Synchronous multi-wavelength mode-locked laser at 2-μm based on Mamyshev cavity - Gong, Rui; Geng, Yalin; Pei, Li; Wei, Huai (Frontiers in Physics, 2023)
In recent years, 2-μm band lasers have developed rapidly due to their wide range of usage. It is a challenging problem to realize the synchronization of multi-wavelength multi-channel ultrashort pulses for many important applications. In this paper, a 2-μm synchronous multi-wavelength fiber laser is proposed. The laser was constructed based on cascaded Mamyshev regenerators. The multi-cascade nonlinear broadening and offset filtering can act as a saturable absorber, enabling mode locking, and resolving the issues of gain competition and synchronous output encountered in traditional multi-wavelength lasers. A stable synchronous multi-wavelength mode-locked laser was realized through numerical simulation. The laser can provide six-channel ultrashort pulses with a wavelength interval of 5 nm (the central wavelengths range from 2000 nm to 2025 nm). The peak power and duration of the output pulses are respectively 0.1–0.25 kW (intracavity peak power 0.4–1.1 kW for coupler ratio is 20:80) and ∼1.1 ps. Design principles and the effects of various parameters such as the filter, the fiber length, etc., on the optimization of the laser are analyzed and discussed.